Near‐infrared spectroscopy detects age‐related differences in skeletal muscle oxidative function: promising implications for geroscience. Issue 3 (7th February 2018) - Chung, Susie; Rosenberry, Ryan; Ryan, Terence E.; Munson, Madison; Dombrowsky, Thomas; Park, Suwon; Nasirian, Aida; Haykowsky, Mark J.; Nelson, Michael D.
Abstract: Age is the greatest risk factor for chronic disease and is associated with a marked decline in functional capacity and quality of life. A key factor contributing to loss of function in older adults is the decline in skeletal muscle function. While the exact mechanism(s) remains incompletely understood, age‐related mitochondrial dysfunction is thought to play a major role. To explore this question further, we studied 15 independently living seniors (age: 72 ± 5 years; m/f: 4/11; BMI: 27.6 ± 5.9) and 17 young volunteers (age: 25 ± 4 years; m/f: 8/9; BMI: 24.0 ± 3.3). Skeletal muscle oxidative function was measured in forearm muscle from the recovery kinetics of muscle oxygen consumption using near‐infrared spectroscopy (NIRS). Muscle oxygen consumption was calculated as the slope of change in hemoglobin saturation during a series of rapid, supra‐systolic arterial cuff occlusions following a brief bout of exercise. Aging was associated with a significant prolongation of the time constant of oxidative recovery following exercise (51.8 ± 5.4 sec vs. 37.1 ± 2.1 sec, P = 0.04, old vs. young, respectively). This finding suggests an overall reduction in mitochondrial function with age in nonlocomotor skeletal muscle. That these data were obtained using NIRS holds great promise in gerontology for quantitative assessment of skeletal muscle oxidative function at the bed side or clinic. Abstract : The data herein provide initial proof‐of‐concept for a cost‐effective, noninvasive imaging approach to assess age‐related changes in skeletal muscle oxidative function.